Impact assessment of farm ponds in Maan River Catchment-A case study - K.D., GHARDE; BISEN, Y.; GAWANDE, P.A. (Journal of Soil and Water Conservation, 2023)
The farm pond is rainwater harvesting structures adopting through different government schemes on farmer’s field to make rainwater available during drought period and increase the crop productivity of the crops during Kharif ad Rabi season. There were more than 10 lakh farm ponds constructed in different village at farmers field during 2014-2019. There is need to analyzed the impact of this technology on livelihood of the farmers. Accordingly, 110 beneficiary’s farmers were interacted of 13 villages of Patur (7 villages) and Balapur (6 villages) Taluka of Akola District belong to Mann Catchment. The farm ponds were found very useful (40.81%) to useful (50.61%) for providing supplemental irrigation, providing drinking water to animal, rainwater harvesting, reducing waiting period for sowing of crop during Kharif and Rabi season. The 24.55 percent respondent reported harvested rain water used for supplanted irrigation to crop, for drinking purposes (20.0 per cent), for ground water recharging (32.73 per cent), for cultivating Indian major corps (IMC) used i. e fish (3.63 per cent) and the pond not useful at all (13.64 per cent). There was a change in occupation annual income, cropping intensity and productivity of major crops viz cotton and gram to the tune of 31.68, 99.23, 45.08, 128.43 and 95.95 per cent, respectively after construction of farm ponds. When impact as a whole was considered, there was total impact of 80.07 per cent of farm ponds on the beneficiaries.